Factors influencing corporate social responsibility disclosure (CSRD) by Libyan state-owned enterprises (SOEs) - Najeb Masoud; Anu Vij (Cogent Business & Management, 2021)
This paper examines the relationship between selected firm-specific variables and the extent of corporate social responsibility (CSR) disclosures by Libyan state-owned enterprises (SOEs). The initial sample in this study consists of the 310 annual reports from 95 firms over a period of eight years from 2010 to 2018 inclusive. A content analysis approach of the firms' annual reports is applied using a CSR disclosure index based on the Global Reporting Initiative guidelines. The factors in this study are analysed against the extent of CSR disclosures by SOEs using multiple regression. The main finding from the content analysis indicates that the extent of CSR disclosures made by SOEs in their annual reports is mostly descriptive, with charity and donation being the most disclosed items. The main findings from the correlation and regression analyses show that four of the eight proposed independent variables - firm sizes, firm age, type of sector, and CSR responsibilities-are statistically significant and positively related to the dependent variable CSR disclosure. With respect to the profile of SOE managers, those who are exercise responsibility in areas of CSR appear to have a significant influence on information disclosure in this respect, perhaps because their profession makes them more aware of such issues. The paper offers significant contributions to the extant literature by examining whether there are any effects of CSR disclosure practices by SOEs and expands the pool of CSR knowledge in the developing country context, especially in the public sector. This study provides fruitful implications for policy-makers and practitioners about state holdings, which may either hinder, or enhance corporate social performance.
Keywords: 650; CSR disclosure; CSR responsibilities; SOEs; Public-sector; Libya